Pengaplikasian Pembuatan Molding Untuk Pembuatan Sendok Plastik Berbahan Hdpe Guna Keperluan Industri Rumahan Dengan Bantuan CAD/CAM/CNC - Jemi Haryono; Aa Santosa; Rizal Hanifi (Peneliti.net, 2023)
In recent years, the use of polymers has increased in various industries. Not only in the home industry, but polymers have also played a big role in the automotive industry. Examples of polymer applications in the automotive industry include the use of headers on mirrors and vehicle plates. There have been many studies that reveal the properties of polymers that can be equated with metal materials. In addition, the availability of polymers is considered easier to obtain than metal materials. It's just that there is still a need for more research in this regard. Plastics processing involves many of the same operations as metal production. Plastics can be molded, poured, and shaped as well as processed by machining and joining. Plastic raw materials are often found in the form of pellets or powder. Plastics are also available in the form of sheets, plates, bars and pipes. Plastic processing methods can be done by: extrusion, injection molding, casting, thermoforming, blow molding and others. Injection molding is one way that can be done in producing components from plastic materials. The injection molding machine consists of several parts, such as: nozzle, hopper, heating elements, mold and piston. After 600 minutes of manufacturing process using several processes such as facing process, contouring process, finishing process, drilling process, and programming process, a molding is produced. spoon for home industry scale. The cost of making 1 molding spoon is Rp. 4,000,000.00 and the cost of purchasing materials is Rp. 184,000.00. So that the total cost of making spoon molding is Rp. 4,184,000.00.